114 Subacute axonal and demyelinating peripheral neuropathy complicating Duodopa therapy for Parkinson's disease. Issue 3 (9th February 2012) - Kobylecki, C; Marshall, A G; Gosal, D; Silverdale, M A; Kellett, M W
Abstract : Levodopa-carbidopa intestinal infusion (Duodopa) has proven efficacy in the management of motor complications of Parkinson's disease (PD). Recent case reports describe subacute axonal neuropathy in patients receiving Duodopa. We report three cases of subacute peripheral neuropathy complicating Duodopa therapy, including two in whom demyelinating features were identified. Three patients with PD (age range 48–68 years) treated with Duodopa (1740–2240  mg/day) presented with a 6–12-week history of paraesthesiae and numbness in upper and lower limbs, with preserved power. Neurophysiological examination revealed absent or attenuated sensory responses in all cases; in two cases there was significant motor conduction slowing and F-wave prolongation. Homocysteine levels were elevated in all patients, and vitamin B12 level in one patient was borderline. There was no evidence of any alternative underlying cause for neuropathy, and CSF examination was normal in both patients with demyelinating features. All patients improved or stabilised clinically following treatment including vitamin B12 supplementation; two stopped Duodopa, while one continued Duodopa along with prednisolone. Duodopa-induced neuropathy may have a demyelinating component, in contrast to previous reports in the literature. Given the putative association between levodopa use, raised homocysteine levels and peripheral neuropathy, clinicians should be alert to this potential complication of Duodopa therapy.